Comparison of Operative Parameters During Fixation of Intertrochanteric Fractures with Proximal Femoral Nail and Dynamic Hip Screw - Kashif Ali Shaikh, Awes Ahmed, Kamran Bahadur Khan, Fahad Noor Memon, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The aim of the study was to evaluate the surgical characteristics of the proximal femoral nail and dynamic hip screw stabilisation for intertrochanteric fractures. Methods: After the ethical approval from the institutional review board, this randomized controlled trial, was conducted at Orthopaedic Department, Jinnah Post Graduate Medical Centre, Karachi, from 29th July 2018 to 28th January 2019 through the non-probability consecutive sampling, 100 participants were recruited for the present study. Radiographs of the pelvis with both hips anteroposterior view and traction-internal rotation view were taken. proximal femoral nail was used in group A while dynamic hip screw was used in group B. At the end of the surgery, time and blood loss were calculated and independent t-test was applied for comparison. Effects were addressed through Stratification. P-value ≤0.05 was taken as significant. Results: There were 72% male and 28% female patients in group-A and 68% male and 32% female patients in group-B. The mean fracture duration in group-A and group-B was 3.52±1.41days and 3.54±1.45 days respectively. Mean operative time in group-A and group-B was 91.32±8.10 minutes and 73.20±12.52 minutes respectively while mean intraoperative blood loss was 188.34±25.80 ml and 255.44±14.56 ml in group-A and group- B respectively. These differences were found significant. Conclusion: Group A had a longer mean surgical duration and considerably less mean intra-operative blood loss as compared to group B. Keywords: Operative Parameters, Intertrochanteric Fractures, Proximal Femoral Nail, Dynamic Hip Screw